A NEED OF BETTER PHARMACOVIGILANCE SYSTEM IN INDIA - Masurkar, Prajakta (Asian Journal of Pharmaceutical and Clinical Research, 2017)
India is one of the top producers of generics globally and is currently being recognized as the pharmacy of the worldâ€ for the generic drug products. Thus, there is a need that it has best health-care systems in place to regulate and provide better quality drugs by monitoring the possible risk associated with the use of drugs. Being the generic hub, physicians, pharmacists, etc., should be erudite to provide an alternative cost-effective generic medicine, which is one of the education-related aspects of pharmacovigilance. We need a more systematic approach to surveillance of drug-related problems, which is at the heart of pharmacovigilance. The health-care system requires new processes to understand the risk-benefit ratio of drugs. The challenges in implementation of better pharmacovigilance in country due to nonavailability of trained staff in pharmacovigilance, lack of training of health-care professionals on drug safety, and adverse drug reaction reporting which comprises adverse interactions of medicines with chemicals, other medicines, and food are often neglected leading to under-reporting by health-care professionals as well as patients, lack of expertise, etc., should be overcome by Indian regulatory body via practical oriented knowledge-based system. The web market monitoring, global electronic database, education, association of stakeholders and regulation of herbal medicines standards and allied medicinal systems are vital restructurings needed to be introduced for a better pharmacovigilance system in India. Keywords: Pharmacovigilance, India.